Secure Login Mechanism for Online Banking - Ahmad Syahir; Chuah Chai Wen (Society of Visual Informatics, 2018)
Login is one of the important security features in online banking. This research investigates the mechanism for an existing online banking in Malaysia including the design of the login mechanism, the encryption algorithm used for the password Â and the security level of the login mechanism. This research provides a result of analyzing data between five online banking in terms of their security features. These analyzing data will be used for proposing secure password encryption in online banking. The mathematic is used to evaluate the security level for these secure login applications. Output from the mathematical analysis is the probability that the adversary may break the security of login application.